Penerapan Model Pembelajaran Problem Based Learning dalam Meningkatkan Hasil Belajar pada Mata Pelajaran PAI di SMP N 1 Tigo Nagari - Irawan, Munria (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education (PAI) by applying the Problem Based Learning model on the topic of belief in angels. The research was conducted using a classroom action research (CAR) approach, implemented over two cycles. In the first cycle, student learning outcomes showed some difficulties, but in the second cycle, there was a significant improvement in both learning outcomes and student participation. The final test results of the second cycle showed an average score of 70.63, with a classical completeness percentage of 68.75%. Although some students were still less active in group discussions or hesitant to present, the implementation of the PBL model was proven effective in enhancing students’ understanding of the material and their involvement in the learning process. This study recommends further improvements in the next cycle to achieve more optimal results.